Tinjauan Hukum Hak Waris Anak Diluar Nikah Berdasarkan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Amrun Kahar (Jurnal Hukum Volkgeist, 2017)
The presence of a child outside of marriage/marriage will be a matter of sufficient concern for women who give birth to or for local people. This research will be conducted on Religious Pasarwajo Court, is based on the consideration that the data and information necessary and relevant to the issues in the research in, can be poroleh easily. The research results showed that the inheritance of the child outside of marriage based on law No. 1 year 1974 about marriage is a whole child outside mating born outside the marriage provision provision or requirement contained in article 2 paragraph (1) and paragraph (2) of law number 1 Year 1974 about marriage. Berdasrkan research results beyond the kawini children of the author, who is not at all in a marriage that is valid not included in the terms of mutual recognition of inherited, except by a man that it was his son who followed by the existence of DNA evidence and a blood test based on the decision of the constitutional Number Mahkama. 46/PUU-VIII/2010.